In-situ realtime study of zinc selenide nanoparticles sustained by polypyrrole in alkaline water oxidation - Mishra R.; Malviya M. (My University, 2025)
Interest in metal electrodeposition for synthesizing customized nanomaterials has resurged, particularly for applications such as sensors and fuel cells. The present study involved the synthesis of ZnSe nanoparticles (via hydrothermal method) while polypyrrole and novel composite Ppy@ZnSePpy@Ppy (via sequential electrodeposition technique) on a glassy carbon (GC) electrode and their physiochemical, electrochemical, and operando spectro-electrochemical characterizations towards oxygen evolution reaction (OER). Results indicated that ZnSe nanoparticles are well embedded within the Ppy layers and during OER the composite electrocatalyst approached 398 mV at 10 mA cm−2 and exhibited Tafel value (b ∼ 75 mV dec−1) with ECSA (0.03) which shows better results than other two. In addition, the operando spectro-electrochemical spectra of the composite revealed the significant generation of active intermediate oxygen species of selenium and Zn2+. The important feature of the current work is the disclosure of Se's questionable role and species involved in OER found to be Se4+. © 2024